Problemy z przygotowaniem wniosków i wdrażaniem ZPORR w woj. dolnośląskim w pierwszym roku korzystania z funduszy strukturalnych - Piasecka, Kamila (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this article is to show problems of beneficiaries and implementing institutions which are involved in managing the Integrated Regional Operational Programme in Lower Silesian Voivodship. The period of this study concerns the first year of using structural funds by the regions in Poland. The article regards essential information about the Integrated Regional Operational Programme, institutions which take part in this programme and about assignments of these institutions. The emerging problems are adjusted to corresponding institutions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 257-263